2005
DOI: 10.1200/jco.2005.01.6378
|View full text |Cite
|
Sign up to set email alerts
|

Length of Stay and Mortality Associated With Febrile Neutropenia Among Children With Cancer

Abstract: Race, age group, year of discharge, associated complications, and cancer type were significantly associated with risk of longer los and mortality. These factors may potentially help in identifying high-risk patients who might benefit from targeted antibiotic therapy or prophylactic hematopoietic growth factor support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
5
10

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 24 publications
6
104
5
10
Order By: Relevance
“…[13] In the current study, the risk of composite AE outcome was higher in children younger than 5 years compared to those who were older (61% vs. 39%; OR 1.83), although the result was not statistically significant (p=0.172).…”
Section: Resultscontrasting
confidence: 43%
See 3 more Smart Citations
“…[13] In the current study, the risk of composite AE outcome was higher in children younger than 5 years compared to those who were older (61% vs. 39%; OR 1.83), although the result was not statistically significant (p=0.172).…”
Section: Resultscontrasting
confidence: 43%
“…A similar study reported three-fold longer length of stay as well as death in AML patients as compared to ALL [13]. A diagnosis of lymphoma and sarcomas was associated with a significant reduction in the risk of composite adverse outcome.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…En estudios norteamericanos se encuentra que hasta el 34% de los casos de neutropenia febril corresponden a pacientes con leucemia linfoide aguda, seguido de leucemia mieloide aguda con un 11% y linfoma no Hodgkin con un 9%. Otros tumores en los cuales se ha reportado esta entidad son las neoplasias del sistema nervioso central en el 6%, riñón en el 3% y tumores gonadales 16 . Estudios realizados en Colombia muestran cifras similares, encontrando que el 47% de los casos de neutropenia febril corresponden a pacientes con leucemia linfoide aguda, linfoma no Hodgkin en el 21%, leucemia mieloide aguda en el 10% y menos frecuentemente en el tumor de Wilms, retinoblastoma, rabdomiosarcoma y tumores del sistema nervioso central 15 .…”
Section: Neutropeniaunclassified